Heart failure ‘the cancer of the heart’: the prognostic role of the HLM score - Paolo Severino; Massimo Mancone; Andrea D'Amato; Marco Valerio Mariani; Silvia Prosperi; Danilo Alunni Fegatelli; Lucia Ilaria Birtolo; Danilo Angotti; Alberto Milanese; Enrico Cerrato; Viviana Maestrini; Carmine Pizzi; et al. (ESC Heart Failure, 2024)
Abstract Aims The multi‐systemic effects of heart failure (HF) resemble the spread observed during cancer. We propose a new score, named HLM, analogous to the TNM classification used in oncology, to assess the prognosis of HF. HLM refers to H: heart damage, L: lung involvement, and M: systemic multiorgan involvement. The aim was to compare the HLM score to the conventional New York Heart Association (NYHA) classification, American College of Cardiology/American Heart Association (ACC/AHA) stages, and left ventricular ejection fraction (LVEF), to assess the most accurate prognostic tool for HF patients. Methods and results We performed a multicentre, observational, prospective study of consecutive patients admitted for HF. Heart, lung, and other organ function parameters were collected. Each patient was classified according to the HLM score, NYHA classification, ACC/AHA stages, and LVEF assessed by transthoracic echocardiography. The follow‐up period was 12 months. The primary endpoint was a composite of all‐cause death and rehospitalization due to HF. A total of 1720 patients who completed the 12 month follow‐up period have been enrolled in the study. 520 (30.2%) patients experienced the composite endpoint of all‐cause death and rehospitalization due to HF. 540 (31.4%) patients were female. The mean age of the study population was 70.5 ± 12.9. The mean LVEF at admission was 42.5 ± 13%. Regarding the population distribution across the spectrum of HLM score stages, 373 (21.7%) patients were included in the HLM‐1, 507 (29.5%) in the HLM‐2, 587 (34.1%) in the HLM‐3, and 253 (14.7%) in the HLM‐4. HLM was the most accurate score to predict the primary endpoint at 12 months. The area under the receiver operating characteristic curve (AUC) was greater for the HLM score compared with the NYHA classification, ACC/AHA stages, or LVEF, regarding the composite endpoint (HLM = 0.645; NYHA = 0.580; ACC/AHA = 0.589; LVEF = 0.572). The AUC of the HLM score was significantly better compared with the LVEF (P = 0.002), ACC/AHA (P = 0.029), and NYHA (P = 0.009) AUC. Conclusions The HLM score has a greater prognostic power compared with the NYHA classification, ACC/AHA stages, and LVEF assessed by transthoracic echocardiography in terms of the composite endpoint of all‐cause death and rehospitalization due to HF at 12 months of follow‐up.